The Importance of Materials Data and Modelling Parameters in an FE Simulation of Linear Friction Welding - R. Turner; F. Schroeder; R. M. Ward; J. W. Brooks (Advances in Materials Science and Engineering, 2014)
Linear friction welding has become a key technology in the aeroengine industry due to its capability to produce blisk components. Finite element (FE) simulation of linear friction welding applications has been studied in recent years by a number of institutions, using a variety of software codes. Several codes have been demonstrated to be capable of predicting with reasonable accuracy some or all of the critical outputs of friction welding, namely, the thermal loading, plastic deformation, and residual stresses generated. The importance of reliable material data in performing these calculations is paramount. Available material data in the published literature is often restricted to lower temperatures and strain rate regimes. Extrapolation methods used on this data to estimate high temperature properties can lead to uncertainties in the modelled predictions. This paper reviews the approach to materials modelling, including material datasets and material constitutive laws, for FE simulation work in the literature regarding linear friction welding. Best-practice methods for materials constitutive laws, materials data-sets, and the associated experimental temperatures and strain rates used to gather data are suggested. Finally, successfully validated modelled outcomes—when a robust, reliable, and accurate material database has been selected—are demonstrated for a number of the FE methods considered.